Implementasi Media Audio Visual untuk Meningkatkan Pengetahuan Mitigasi Bencana Bagi Siswa - Suwarni; Nurvita; Risma Fadhilla Arsy; Haslita Rahmawati Hasan (Jurusan Pendidikan Geografi FKIP Universitas Halu Oleo, 2024)
The use of audio-visual media is crucial to enhance students' understanding of disaster mitigation material as it can improve students' memory retention. This study aims to determine the effect of utilizing audio-visual media on improving disaster mitigation knowledge among 11th-grade students at Senior High School 10 Sigi. The research used a quasi-experimental method with a non-equivalent control-group design. The research design involved pretests and posttests in both the experimental and control classes. Data analysis techniques included normality tests, homogeneity tests, N-Gain tests, and t-tests. Based on the results of the N-Gain test calculation, the average N-Gain score in the experimental class using audio-visual media was 75.4%, which falls into the high category. Meanwhile, the average N-Gain score in the control class using conventional teaching methods was 49%, which falls into the medium category. The t-test yielded a Sig (2-tailed) value of 0.000 < 0.05, meaning the hypothesis is accepted. Therefore, it can be concluded that audio-visual media significantly impacts improving students' disaster mitigation knowledge at Senior High School 10 Sigi.